2009
DOI: 10.1097/dad.0b013e3181a58234
|View full text |Cite
|
Sign up to set email alerts
|

Viral-Associated Nonmelanoma Skin Cancers: A Review

Abstract: Nonmelanoma skin cancers are the most common malignancies in the United States, with over 1.3 million patients diagnosed yearly. Several types of nonmelanoma skin cancer and precancerous lesions have an associated viral pathogenesis, including epidermodysplasia verruciformis, verrucous carcinoma, bowenoid papulosis, Kaposi sarcoma, squamous cell carcinoma, and, most recently, Merkel cell carcinoma. It is now widely accepted that high-risk human papillomaviruses (HPVs) play a key role in pathogenesis of cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 172 publications
(200 reference statements)
3
74
1
Order By: Relevance
“…3,40 Previous studies concluded that verrucous carcinoma from mucosal areas are related to mucosal HPV types and verrucous carcinoma located in cutaneous areas are not specifically linked to any specific group of HPV. 41 In this study, we found that mucosal types were indeed restricted to mucosal lesions, that is, high-risk HPV in a verrucous carcinoma of the head and neck region and low-risk HPV types in giant condylomas of the anus and vulva, whereas cutaneous HPV types were detected in a verrucous hyperplastic lesion of the penis.…”
Section: Human Papillomavirus In Verrucous Carcinomamentioning
confidence: 51%
“…3,40 Previous studies concluded that verrucous carcinoma from mucosal areas are related to mucosal HPV types and verrucous carcinoma located in cutaneous areas are not specifically linked to any specific group of HPV. 41 In this study, we found that mucosal types were indeed restricted to mucosal lesions, that is, high-risk HPV in a verrucous carcinoma of the head and neck region and low-risk HPV types in giant condylomas of the anus and vulva, whereas cutaneous HPV types were detected in a verrucous hyperplastic lesion of the penis.…”
Section: Human Papillomavirus In Verrucous Carcinomamentioning
confidence: 51%
“…(43,44) However the variable quantity of HPV in immunocompetent individuals can range between 27-70% depending on detection techniques. (32,44) Thus the type of HPV, β-papillomavirus species 2, may be more often associated with cSCC as opposed to the total amount of HPV DNA present. 32 Three theories have been suggested for the mechanism of HPV carcinogenesis: 1) UV radiation induced immunosuppression to explain an enhanced interaction between HPV and UV radiation, 2) E6/E7 oncoprotein-related changes in p53 and Rb tumor suppressor gene, and 3) integration of HPV DNA disrupting genomic stability.…”
Section: Immunologic Altered Host Statementioning
confidence: 99%
“…32 Three theories have been suggested for the mechanism of HPV carcinogenesis: 1) UV radiation induced immunosuppression to explain an enhanced interaction between HPV and UV radiation, 2) E6/E7 oncoprotein-related changes in p53 and Rb tumor suppressor gene, and 3) integration of HPV DNA disrupting genomic stability. (32,45,46) . Viral expression of E6 and E7 oncoproteins can inactivate p53 and Rb tumor suppessor genes, leading to an uncontrolled system of cell proliferation and apoptosis.…”
Section: Immunologic Altered Host Statementioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] Lesion persistency and progression are increased in both animals and humans with genetic, iatrogenic or acquired cell mediated immune deficiencies, such as in patients with severe combined immunodeficiency, [34] in immunosupressed organ recipient patients, [35] in patients with epidermodysplasia verruciformis [35] and sun-exposed sites of patients with non-melanoma skin cancer. [35][36][37] Moreover, HPVs can escape the immune system and down regulate the innate immune signalling pathways. [38] The clearance of high risk HPV types are believed to be harder since these types weaken the immune defences causing infection to continue and progress to neoplasias.…”
Section: Immune Responses To Hpv and Vaccine-induced Protectionmentioning
confidence: 99%